The return of the Beaker folk? Rethinking migration and population change in British prehistory. (December 2021) - Armit, Ian; Reich, David
Abstract: Abstract : Recent aDNA analyses demonstrate that the centuries surrounding the arrival of the Beaker Complex in Britain witnessed a massive turnover in the genetic make-up of the island's population. The genetic data provide information both on the individuals sampled and the ancestral populations from which they derive. Here, the authors consider the archaeological implications of this genetic turnover and propose two hypotheses—Beaker Colonisation and Steppe Drift—reflecting critical differences in conceptualisations of the relationship between objects and genes. These hypotheses establish key directions for future research designed to investigate the underlying social processes involved and raise questions for wider interpretations of population change detected through aDNA analysis.